Upper GI Bleed in a Patient With Cirrhosis of the Liver - Paul Kim; Lea Ann Chen; Daniel Lugassy; Demian Szyld (Association of American Medical Colleges, 2015)
Abstract Introduction This case-based simulation exercise focuses on the evaluation and management of a patient presenting to the emergency department with an upper gastrointestinal (GI) bleed, or more specifically, a variceal bleed. Methods Clinical-year medical students, participated in this high-fidelity simulation during a 3− to 4-day long interclerkship intensive. Students were divided into groups of eight to 10 students, with four to five actively participating in this case, while four to five observed. Those who were participants were expected to manage the care of the patient. Those who observed during the first case then actively participated in the second case. Debriefing materials and references are included. All students actively participated in debrief. Typically, two faculty teach the simulation case. One faculty is from emergency medicine or critical care and is familiar with mannequin controls, as well as acute management of patients. The other faculty is a gastroenterologist who can speak to specific areas of management and is the content expert for the learning objectives. Results After completing 3 months of clinical clerkships, 160 core clinical-year medical students, participated in this simulation. While this case has been used for the past 4 years, evaluation data was only collected for the most recent year. Student evaluations this year indicated that 79% of the objectives were met and 19% were partially met. Three percent stated objectives were not met. Student feedback has been positive, and their varying knowledge and skill level allow the students to teach each other. Discussion This case has been well received by both students and faculty facilitators as an effective way to test students' ability to manage a patient presenting to the emergency department with an upper gastrointestinal (GI) bleed.